MAGNETIC FIELD OF STRANGE STARS - Sedrakian, D.M.; Hayrapetyan, M.V.; Baghdasaryan, D.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
The generation of a magnetic field and its distribution inside a rotating strange star are discussed. The difference between the angular velocities of the superfluid and superconducting quark core and of the normal electron plasma increases because of spin-down of the star and this leads to the generation of a magnetic field. The magnetic field distribution in a star is found for a stationary value of difference of angular velocities of these components. In all parts of the star this field is determined entirely by the total magnetic momentMof the star which can vary from 1031-1034 G·cm3 for some models of compact stars. Also the maximum possible values of magnetic field on the surface of various models of strange dwarfs have been estimated. Depending on configuration parameters, mass M and radius R of the star, the limit of 103-105 G has been established. Such values of magnetic field may be an additional condition for identification of strange dwarfs among the large class of observed white dwarfs.
Keywords: quark matter, strange star, superfluidity, magnetic field